PENGARUH KOMUNIKASI TERAPEUTIK TERHADAP HOSPITALISASI PADA ANAK - Linawati Novikasari; Rika Yulendasari; Eva Maryana (Universitas Malahayati Lampung, 2019)
ABSTRACT: THERAPEUTIC COMMUNICATION ON THE LEVEL OF ANXIETY IN SCHOOL AGE CHILDREN (7-13 YEARS) IN DKT TK IV HOSPITAL 02.07.04 BANDAR LAMPUNG Background: Hospitalization causes the child to experience separation from the family. Children experience anxiety and stress, estimated at more than 50% of 5 million. This makes a child feel fear, feel threatened, lonely, anxious, and anxious.Purose: The influence of therapeutic communication on the level of anxiety in school age children (7-13 years) in DKT TK IV Hospital 02.07.04 Bandar Lampung.Methods: Quantitative research type, quasi experimental design with one group pretest-posttest. In February (2017) children aged 7-13 years who treated were 56 people. If the population is small or to reduce errors in the study then the entire population is sampled. The sampling technique uses accidental sampling. Data taken with observation sheet. Data analysis using t- test.Results: The results before the therapeutic communication was given the average anxiety level due to hospitalization in preschoolers is mean 10.79. Once given is mean 8.11.Conclusion: There is influence of terapeutik communication on the level of anxiety due to hospitalization at school-age children at DKT TK IV Hospital 02.07.04 Bandar Lampung 2017 (t table 2.679 t arithmetic 1,276 p-value = 0.00). With the mean difference value is 2.68 It is suggested to the hospital to improve the skill of the nurse by engaging in seminar or training activity especially related to handling of hospitalization in children. Keywords: Hospitalization, Therapeutic INTISARI: PENGARUH KOMUNIKASI TERAPEUTIK TERHADAP HOSPITALISASI PADA ANAK Latar belakang: Hospitalisasi menyebabkan anak mengalami perpisahan dengan keluarga. anak mengalami kecemasan dan stress, diperkirakan lebih dari 50% dari 5 juta. Hal ini membuat seorang anak akan merasakan ketakutan, merasa terancam, sepi, gelisah, dan cemas.Tujuan: Mengetahui pengaruh komunikasi terapeutik terhadap tingkat kecemasan pada anak sekolah usia (7-13 tahun) di Rumah Sakit DKT TK IV 02.07.04 Bandar Lampung.Metode: Jenis penelitian kuantitatif, desain quasi eksperimen dengan one group pretest-posttest. Dalam bulan Februari (2017) anak usia 7-13 tahun yang di rawat berjumlah 56 orang. Jika populasi sedikit atau untuk mengurangi kesalahan dalam penelitian maka seluruh populasi dijadikan sampel. Teknik sampling menggunakan accidental sampling. Data diambil dengan lembar observasi. Analisa data menggunakan uji t-test.Hasil: Hasil penelitian sebelum diberikan komunikasi terapeutik rata-rata tingkat kecemasan akibat hospitalisasi pada anak usia prasekolah adalah mean 10,79. Setelah diberikan adalah mean 8,11.Kesimpulan: Ada pengaruh komunikasi terapeutik terhadap tingkat kecemasan akibat hospitalisasi pada anak usia sekolah di Rumah Sakit DKT TK IV 02.07.04 Bandar Lampung tahun 2017 (t tabel 2,679 t hitung 1,276 p–value = 0,00). Dengan nilai beda mean adalah 2,68 Disarankan kepada rumah sakit meningkatkan keterampilan perawat dengan mengikutsertakan dalam kegiatan seminar atau pelatihan tentang penanganan hospitalisasi pada anak. Kata Kunci : Hospitalisasi, Komunikasi Terapeutik.